A DNA repair disorder caused by de novo monoallelic DDB1 variants is associated with a neurodevelopmental syndrome. - White, Susan M; Bhoj, Elizabeth; Nellaker, Christoffer; Lachmeijer, Augusta M A; Marshall, Aren E; Boycott, Kym M; Li, Dong; Smith, Wendy; Hartley, Taila; McBride, Arran; Ernst, Michelle E; May, Alison S; et al. (Am J Hum Genet, 2021)
The DNA damage-binding protein 1 (DDB1) is part of the CUL4-DDB1 ubiquitin E3 ligase complex (CRL4), which is essential for DNA repair, chromatin remodeling, DNA replication, and signal transduction. Loss-of-function variants in genes encoding the complex components CUL4 and PHIP have been reported to cause syndromic intellectual disability with hypotonia and obesity, but no phenotype has been reported in association with DDB1 variants. Here, we report eight unrelated individuals, identified through Matchmaker Exchange, with de novo monoallelic variants in DDB1, including one recurrent variant in four individuals. The affected individuals have a consistent phenotype of hypotonia, mild to moderate intellectual disability, and similar facies, including horizontal or slightly bowed eyebrows, deep-set eyes, full cheeks, a short nose, and large, fleshy and forward-facing earlobes, demonstrated in the composite face generated from the cohort. Digital anomalies, including brachydactyly and syndactyly, were common. Three older individuals have obesity. We show that cells derived from affected individuals have altered DDB1 function resulting in abnormal DNA damage signatures and histone methylation following UV-induced DNA damage. Overall, our study adds to the growing family of neurodevelopmental phenotypes mediated by disruption of the CRL4 ubiquitin ligase pathway and begins to delineate the phenotypic and molecular effects of DDB1 misregulation.
Keywords: Adolescent; Alleles; Child; Child, Preschool; DNA Repair; DNA-Binding Proteins; Female; Humans; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Syndrome

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.